US Pilot Study of Lumbar to Sacral Nerve Rerouting to Restore Voiding and Bowel Function in Spina Bifida: 3-Year Experience - Kenneth M. Peters; Holly Gilmer; Kevin Feber; Benjamin J. Girdler; William Nantau; Gary Trock; Kim A. Killinger; Judith A. Boura (Advances in Urology)
Objective. To report our experience with creating a skin-central nervous system-bladder reflex arc with intradural lumbar to sacral motor root microanastomosis to restore bladder/bowel function in spina bifida patients. Methods. Urinary/bowel changes from baseline to three years were evaluated with questionnaires, voiding diaries, urodynamics (UDS), and renal function studies. Treatment response was defined as CIC ≤ once/day with stable renal function, voiding efficiency > 50%, and no worsening of motor function. Results. Of 13 subjects (9 female, median age 8 years), 3 voided small amounts at baseline, one voided 200 cc (voiding efficiency 32%), 4/13 reported normal bowels, and 2/13 were continent of stool. Postoperatively, all had transient lower extremity weakness; one developed permanent foot drop. Over three years, renal function remained stable and mean maximum cystometric capacity (MCC) increased (P=0.0135). In the 10 that returned at 3 years, 7 were treatment responders and 9 had discontinued antimuscarinics, but most still leaked urine. Only 2/8 with baseline neurogenic detrusor overactivity (NDO) still had NDO, all 3 with compliance <10 mL/cm H2O had normalized, 7/10 considered their bowels normal, 5/10 were continent of stool, and 8/10 would undergo the procedure again. Conclusion. Lumbar to sacral nerve rerouting can improve elimination in spina bifida patients. This trial is registered with ClinicalTrials.gov NCT00378664.